EVALUATION OF ANTIFUNGAL ACTIVITY OF SATUREJA MONTANA ESSENTIAL OIL BEFORE AND AFTER INCLUSION IN BETA-CYCLODEXTRINE - Haloc I., Entela; Toska, Vilma; Baldisserotto, Anna; Goci, Enkelejda; Vertuani, Silvia; Manfredini, Stefano (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The aim of this study is the evaluation of the antifungal activity of Satureja montana essential oil collected in north of Albania, and how it is affected by microencapsulation in Î²-cyclodextrin (Î²-CD). Methods: GC/FID spectrometry analysis of the isolated oil was used. The Â antifungal activities of essential oil before and after microencapsulation were individually evaluated against following dermatophytes M.gypseum, M.canis, A.cajetani, T.violaceum, T.mentagrophytes, E.floccosum,T. Rubrum, T. tonsurans and phytopatogens B.cinerea and P.oryzae using a disc diffusion method. Results: GC/FID analyses resulted in the identification of twentyone compounds in the oil of Satureja Montana essential oil. Carvacrol was the major constituent of the S. montana oil (around 60 %). Other important compounds were the monoterpenic hydrocarbons p-cymene, y- terpinene and the oxygenated compounds borneol. Maximum activity of Satureja montana oil was observed against T.violaceum, T. Rubrum, T. tonsurans, T.mentagrophytes and P.oryzae (inhibition zone > 70 %). Conclusion: From the results is evident that microencapsulation does not change the antifungal activity of essential oil, this should consent to achieve the optimal antifungal activity with minimum side effects of essential oil, and improved stability upon storage due to benefits of microencapsulation in Î²-cyclodextrine. Moreover, after encapsulation improved activity were obtained (inhibition zone > 70)